2011
DOI: 10.1111/j.1439-037x.2011.00478.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single and Multifactor Treatments with Elevated Temperature, CO2 and Ozone on Oilseed Rape and Barley

Abstract: We investigated the effect of elevated [CO2], [O3] and temperature on plant productivity and if these climate factors interacted with each other in multifactor treatments. The climate effects were studied in 14 different cultivars/lines of European spring oilseed rape (Brassica napus L.) and spring barley (Hordeum vulgare L.). Seven genotypes of each species were cultivated in six single‐ and multifactor treatments with ambient or elevated CO2 (385 ppm and 700 ppm), O3 (20 ppb and 60 ppb) and temperature (12/1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 46 publications
(44 reference statements)
9
58
0
Order By: Relevance
“…The positive effect of elevated [CO 2 ] is clearly reduced, when combined with a temperature elevation of 5°C. Clausen et al (2011) found a yield reduction in well watered barley of 14 % from a multifactor treatment with the same levels of elevated [CO 2 ] and temperature, while we observed a 53 % reduction in yield in the presumably water-limited multifactor treatment. In their review of potential future changes to arable crops, Jaggard et al (2010) stated that elevated [CO 2 ] increases water use efficiency, and thereby the negative impacts of higher temperatures on crops would be approximately cancelled out.…”
Section: Discussionmentioning
confidence: 39%
See 1 more Smart Citation
“…The positive effect of elevated [CO 2 ] is clearly reduced, when combined with a temperature elevation of 5°C. Clausen et al (2011) found a yield reduction in well watered barley of 14 % from a multifactor treatment with the same levels of elevated [CO 2 ] and temperature, while we observed a 53 % reduction in yield in the presumably water-limited multifactor treatment. In their review of potential future changes to arable crops, Jaggard et al (2010) stated that elevated [CO 2 ] increases water use efficiency, and thereby the negative impacts of higher temperatures on crops would be approximately cancelled out.…”
Section: Discussionmentioning
confidence: 39%
“…Clausen et al (2011) recorded a reduction in yield of 27 % from a similar temperature treatment with barley, but as mentioned above plants in their experiment experienced little or no water limitation. In line with that, negative effects of high temperature will get stronger under conditions of low rainfall or drought (IPCC 2007).…”
Section: Discussionmentioning
confidence: 72%
“…In barley, decreases in total above-ground biomass and grain yield have been observed under elevated temperatures (Clausen et al 2011). Högy et al (2013) reported decrease of grain yield, grain number per ear and thousand-grain weight under elevated temperature.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of multi-factor treatment on crop yield have been included at experimental level, e.g. for oilseed rape (Clausen et al, 2011;Frenck et al, 2013Frenck et al, , 2011 and spring barley (Alemayehu et al, 2013;Clausen et al, 2011). Studies of single-factors are more numerous than multi-factor, with the consequence that simulation studies, predicting the primary production of the future, build on the response to single-factor studies, but considerable uncertainty is embedded in the predictions.…”
Section: Crop Yieldmentioning
confidence: 99%
“…This facility was used to perform experiments, analyzing both the production and quality of spring barley and oilseed rape in future climate scenarios (e.g. Alemayehu et al, 2013;Clausen et al, 2011;Frenck et al, 2013Frenck et al, , 2011 under single-and multi-factor treatments. According to IPCC AR5, we are currently approaching the worst-case scenario Representative Concentration Pathway 8.5 (RCP8.5), unless actions are taken collectively in the very near future.…”
Section: Case Study: Spring Barley Cultivation In Denmark Under Futurmentioning
confidence: 99%